Direct measurement of oleate adsorption on hematite and its consequences for flotation. (15th March 2018) - Quast, Keith
Highlights: Direct measurement of oleate on hematite removes the uncertainty of its non-mineral adsorption. At pH 4, oleate formed a monolayer on hematite at the CMC. Monolayer coverage on unfloated material is always less than on floated material. Coadsorption of ionic and molecular oleate species has been proposed near the pKa of oleic acid. Abstract: The direct measurement of adsorbed oleate onto hematite removes the uncertainty of depletion of oleate onto non-hematite surfaces. Direct measurement of oleate onto hematite at pH 4 and as a function of pH at constant oleate addition was made using Differential Scanning Calorimetry. Oleate adsorption measurements were conducted on conditioned, concentrate and tailing samples, corrected for their surface areas. Adsorption measurements were complemented by flotation tests. At pH 4, oleate adsorption on conditioned samples reached a complete monolayer by vertical orientation at the critical micelle concentration (CMC) of the oleate. The onset of multilayer adsorption by vertical orientation on the concentrate samples was determined at the CMC, and monolayer coverage on the non-floated material was always less than one monolayer under two-point and vertical oleate orientation. Flotation recovery of hematite at pH 4 remained high under equilibrium oleate concentrations above the critical hemi-micelle concentration of oleate. Oleate adsorption on hematite as a function of pH showed maxima at pH 4 and 9, suggesting co-adsorption of molecular and ionic oleate species at pH 4. Hematite flotation with 10 −4 molar oleate addition was high for pH values above 4.